Restoration of Declined Immune Responses and Hyperlipidemia by Rubus occidenalis in Diet-Induced Obese Mice - Lee, Youngjoo (Biomol Ther (Seoul), 2017)
Hyperlipidemia, which is closely associated with a fatty diet and aging, is commonly observed in the western and aged society. Therefore, a novel therapeutic approach for this disease is critical, and an immunological view has been suggested as a novel strategy, because hyperlipidemia is closely associated with inflammation and immune dysfunction. In this study, the effects of an aqueous extract of Rubus occidentalis (RO) in obese mice were investigated using immunological indexes. The mice were fed a high-fat diet (HFD) to induce hyperlipidemia, which was confirmed by biochemical analysis and examination of the mouse physiology. Two different doses of RO and rosuvastatin, a cholesterol synthesis inhibitor used as a control, were orally administered. Disturbances in immune cellularity as well as lymphocyte proliferation and cytokine production were significantly normalized by oral administration of RO, which also decreased the elevated serum tumor necrosis factor (TNF)-α level and total cholesterol. The specific immune-related actions of RO comprised considerable improvement in cytotoxic T cell killing functions and regulation of antibody production to within the normal range. The immunological evidence confirms the significant cholesterol-lowering effect of RO, suggesting its potential as a novel therapeutic agent for hyperlipidemia and associated immune decline.